Sensitivity study of weather research and forecasting physical schemes and evaluation of cool coating effects in Singapore by weather research and forecasting coupled with urban canopy model simulations - Zhou, Mandi (2021)
Mesoscale meteorological modeling was conducted to evaluate air temperature at 2‐m above surface (T2), wind speed/direction, and relative humidity (RH) in Singapore, a tropical city, for a dry period. A sensitivity study was conducted to determine the best combination of schemes for the physical modules. The model was used to study the urban heat island (UHI) effect and urban cooling effect by applying cool coating on various urban surfaces. Maximum UHI intensity of 3.2°C is found at nighttime (21:00) at a hot spot in the Commercial/Industrial area. At nighttime, when the UHI effect is generally more intense than daytime, applying cool coating on all urban surfaces can reduce the UHI effect by about 30% in residential areas and about 6% in commercial/industrial areas. Maximum T2 reduction of 3.1°C and surface skin temperature (TSK) reduction of 9.8°C due to cool coating is found at 13:00 at certain locations. The cool urban surfaces reduce radiative heat absorption during daytime, reducing heat storage in urban structures. This leads to subsequent reduction of stored heat release from urban structures, mitigating UHI effect during nighttime. Applying cool coating on horizontal surfaces (roofs and roads) provides more cooling effect than vertical surfaces (walls). Cool roofs provide more cooling effect than cool roads since roofs cover more urban horizontal surfaces than roads do in the current setting. Part of the radiation reflected by cool roads could be absorbed by other urban structures, reducing its cooling effect as compared to cool roofs.